2020
DOI: 10.1002/jmrs.398
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand radiation therapists’ perceptions of peer group supervision as a tool to reduce burnout symptoms in the clinical setting

Abstract: Introduction Research indicates that radiation therapists (RTs) are at risk of burnout and that there is a lack of evidence on effective coping strategies for managing work‐related stressors within this workforce. Peer group supervision (PGS) is a useful tool in assisting staff to manage stress in the clinical setting, improve reflective practice and provide support. The aim of this research was to investigate New Zealand (NZ) RTs’ perceptions of participating in PGS. Methods In‐service training on PGS was off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 16 publications
(43 reference statements)
2
14
0
Order By: Relevance
“…Group clinical supervision assisted managers to access the formative and restorative functions of clinical supervision. Other researchers have found that group clinical supervision can be used to develop leadership skills 24,40 . Group clinical supervision could be used to address the gap of professional development and peer support for allied health managers and senior allied health clinicians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Group clinical supervision assisted managers to access the formative and restorative functions of clinical supervision. Other researchers have found that group clinical supervision can be used to develop leadership skills 24,40 . Group clinical supervision could be used to address the gap of professional development and peer support for allied health managers and senior allied health clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Using a trainer who was experienced in group clinical supervision and who used an experiential learning approach improved the facilitators’ understanding of the group supervision model and increased their confidence in establishing the groups. A recent study of peer group supervision for radiation therapists in New Zealand reported that some participants were dissatisfied with the model in groups that were not well facilitated and consequently had a lack of clarity around the group structure and leadership 24 . Regardless of whether a peer or supervisor‐led model is used, adequate preparation and training of those who are facilitating or leading group clinical supervision are required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study showed interventions like the compassion fatigue resiliency program are effective, feasible, and scalable 26 . Another study showed that peer‐group supervision was helpful to improve the clinicians’ practice and to reduce their work‐related stress and burnout symptoms 27 …”
Section: Discussionmentioning
confidence: 99%
“…To be effective, groups need to adhere to group processes and the agreed structure, and participants need a clear understanding of what they want to achieve from each PGS meeting. 11,13 Overall, the NZ RTs responded positively to PGS, 13 which prompted academic staff to implement PGS into the Bachelor of Radiation Therapy (BRT) programme. The BRT is a three-year degree offered at the University of Otago, Wellington campus and is the only Radiation Therapy programme in NZ.…”
Section: Introductionmentioning
confidence: 99%